Development of Mathematics E-Books in Improving Mathematical Literacy and Entrepreneurial Spirit - Rizki Amalia; Fadilah Fadilah; Mamay Komarudin; Jaka Wijaya Kusuma (STAI Hubbulwathan Duri, 2021)
This study aimed to create an e-book on mathematics learning for vocational high school students in grade XI, complete with liner program material, using the ADDIE model development methodology (Analysis, Design, Development, Implementation, Evaluation). Based on the findings of the development of e-books on linear programming material for grade XI students at vocational high school in Langsa Aceh majoring in Online Business and Marketing, it can be concluded that the media is valid for use in learning mathematics with linear programming materials, then effective in improving mathematical literacy and entrepreneurial spirit. Finally, practical media is used in mathematics learning, among other conclusions.